Work social support, work engagement and their impacts on multiple performance outcomes. Issue 6 (17th December 2019) - Talebzadeh, Niusha; Karatepe, Osman M.
Abstract : Purpose: The purpose of this paper is to propose a research model in which work engagement (WE) mediates the influence of work social support on job satisfaction (JS), in-role performance (IRP), creative performance (CP) and extra-role performance (ERP). Design/methodology/approach: Data were collected from cabin attendants via three surveys two weeks apart and their pursers. The aforesaid relationships were assessed through structural equation modeling. Findings: In general, there is support for the preponderance of hypotheses. Specifically, WE completely mediates the impact of coworker support on JS and IRP, while the impact of supervisor support on CP is completely mediated by WE. WE partly mediates the effect of coworker support on CP and ERP. Furthermore, the effect of supervisor support on JS, IRP and ERP is partly mediated by WE. Practical implications: Management should make sure that the work environment consists of supportive supervisors and coworkers who are trained on how they can enhance the cooperation and collaboration among employees. Management should also create an employee platform where cabin attendants can contribute to service delivery process by sharing their experiences arising from passenger requests and problems. Originality/value: The study extends and contributes to the current service research by assessing the impact of WE simultaneously on three performance outcomes. The study adds to current knowledge by investigating the mediating mechanism linking work social support to the attitudinal and behavioral outcomes. The study also controls the threat of common method variance with at least two procedural remedies, which have been rarely used in the current service research.